Analysis of the Relationship Between Emotional Intelligence and Entrepreneurial Intention: The Mediating Role of Entrepreneurship Practice : Study on State Vocational High School Students in Jombang District - Pratiwi, Galuh Aulia; Wardana, Ludi Wishnu; Restuningdiah, Nurika (Profesional Muda Cendekia Publishing, 2025)
Research Aims: The research aims to examine how emotional intelligence influences the entrepreneurial intentions of state vocational high school students in Jombang District. Specifically, it seeks to understand if entrepreneurship practice serves as a mediating factor in this relationship. By analysing these connections, the study aims to provide insights into ways emotional intelligence can support students' interest in entrepreneurship, potentially guiding the development of targeted educational programs to enhance entrepreneurial skills and mindsets among students. Design/methodology/approach: This research uses a quantitative approach with Partial Least Squares structural equation modelling (PLS-SEM) to predict and confirm the hypotheses given. This research uses google form for data collection on state vocational high school students in Jombang Regency. Respondents in this study were 136 respondents from the three schools that were used as research objects. Research Findings: The results of the analysis of the relationship between emotional intelligence, entrepreneurship practices, and entrepreneurial intention among students of state vocational schools in Jombang Regency, it can be concluded that emotional intelligence plays an important role in influencing entrepreneurial intention, both directly and through entrepreneurship practices. Students with good emotional intelligence are better able to face challenges in entrepreneurship, manage business relationships, and make the right decisions, which in turn increases their desire to go into business. Entrepreneurial practice is also shown to be a factor that strengthens students' intention to become entrepreneurs, especially when they gain real experience in running a business. Theoretical Contribution/Originality: This study contributes to the understanding of how emotional intelligence can foster entrepreneurial intention among students, highlighting the often-overlooked role of practical entrepreneurship experiences. By focusing on vocational high school students in Jombang District, the research sheds light on how hands-on entrepreneurial practice can bridge emotional intelligence and the motivation to pursue entrepreneurship. This originality lies in revealing a potentially powerful pathway that combines personal emotional skills with real-world practice, offering fresh insights for educators and policymakers aiming to nurture young entrepreneurs.